2006
DOI: 10.1155/idog/2006/73073
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Seropositivity and Stool Antigen in Patients With Hyperemesis Gravidarum

Abstract: The objective of this paper is to investigate whether Helicobacter pylori is an etiologic factor in hyperemesis gravidarum. Thirty one patients with hyperemesis gravidarum and twenty nine pregnant controls without hyperemesis gravidarum were included in this prospective study. All pregnant women were examined both for Helicobacter pylori serum immunoglobulin G antibodies (HpIgG Ab), showing chronic infection, and Helicobacter pylori stool antigens (HpSA), showing active gastrointestinal colonization. Chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 17 publications
(15 reference statements)
4
20
0
1
Order By: Relevance
“…17 In Turkey, Karadeniz et al found 68% and 79% H. pylori positivity in subjects with and without HG, respectively (p = not significant). 18 These negative studies are consistent with our findings, where the prevalence of H. pylori in a demographic subsection was unexpectedly found to be significantly higher than the general population and unrelated to HG.…”
Section: Discussionsupporting
confidence: 92%
“…17 In Turkey, Karadeniz et al found 68% and 79% H. pylori positivity in subjects with and without HG, respectively (p = not significant). 18 These negative studies are consistent with our findings, where the prevalence of H. pylori in a demographic subsection was unexpectedly found to be significantly higher than the general population and unrelated to HG.…”
Section: Discussionsupporting
confidence: 92%
“…HG is associated with elevated levels of PAPP-A and free β -hCG, as reported by a recent study in the Turkish population (Derbent et al 2011) and numerous other parameters have been analysed in the literature; among those are allergies suggesting a possible autoimmune component and a restrictive diet (Mullin et al 2012). Helicobacter pylori have also been proposed as a possible aetiological factor for HG but this remains controversial (Karadeniz et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…5 Besides, it has more or less concordance with findings of prospective study carried out by Karadeniz et al (2005) with 22.6 percent prevalence of H. pylori infection among cases. 16 Purposive sampling technique was used for the selection of the study units which hinders the generalization of the study findings. HpSA test is for qualitative detection of H.pylori in stool sample and does not indicate the quantity of the antigen.…”
Section: Discussionmentioning
confidence: 99%